MICROALGAE IN A NUTRITIONAL PERSPECTIVE FOR CONTEXTUALIZED APPROACHES (Fiep Bulletin - online, 2017)
The purpose of this article is to present a reserach based on the scientific content of microalgae in a nutritionalperspective, integrating multidisciplinary knowledge for academia and for community at large. Special mention to the possibilityof incorporating them in activities and strategies for reading and interpretation of scientific texts based on contextualizedapproaches. The methodology consisted in analytical, interpretive and qualitative description of the content of scientificcommunications. The reserach allowed to present content and image of microalgae in a nutritional perspective, potential forleading discussions, with possibility to produce effective contributions by integrating pedagogical practices planned byprofessors and researchers from different fields and levels of education in a contextualized approaches.